At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To determine the value of \( k \) for the polynomial \( p(x) = 2x^2 - k\sqrt{2} x + 1 \) given that the sum of its zeroes is \( \sqrt{2} \), let's follow these steps:
1. Recall the general properties of a polynomial:
For any quadratic polynomial \( ax^2 + bx + c \), the sum of the zeroes (roots) is given by the formula:
[tex]\[ \text{Sum of zeroes} = -\frac{b}{a} \][/tex]
2. Identify the coefficients:
In the polynomial \( p(x) = 2x^2 - k\sqrt{2} x + 1 \), the coefficients are:
[tex]\[ a = 2, \quad b = -k\sqrt{2}, \quad c = 1 \][/tex]
3. Set up the relationship using the sum of the zeroes:
We are given that the sum of the zeroes is \( \sqrt{2} \). According to the formula for the sum of the zeroes, we have:
[tex]\[ -\frac{b}{a} = \sqrt{2} \][/tex]
4. Substitute the coefficients into the formula:
Substituting \( b = -k\sqrt{2} \) and \( a = 2 \) into the formula, we get:
[tex]\[ -\frac{-k\sqrt{2}}{2} = \sqrt{2} \][/tex]
5. Simplify the equation:
[tex]\[ \frac{k\sqrt{2}}{2} = \sqrt{2} \][/tex]
6. Solve for \( k \):
To isolate \( k \), multiply both sides by 2:
[tex]\[ k\sqrt{2} = 2\sqrt{2} \][/tex]
Now, divide both sides by \( \sqrt{2} \):
[tex]\[ k = \frac{2\sqrt{2}}{\sqrt{2}} \][/tex]
Simplify the right-hand side:
[tex]\[ k = 2 \][/tex]
Therefore, the value of [tex]\( k \)[/tex] is [tex]\( \boxed{2} \)[/tex].
1. Recall the general properties of a polynomial:
For any quadratic polynomial \( ax^2 + bx + c \), the sum of the zeroes (roots) is given by the formula:
[tex]\[ \text{Sum of zeroes} = -\frac{b}{a} \][/tex]
2. Identify the coefficients:
In the polynomial \( p(x) = 2x^2 - k\sqrt{2} x + 1 \), the coefficients are:
[tex]\[ a = 2, \quad b = -k\sqrt{2}, \quad c = 1 \][/tex]
3. Set up the relationship using the sum of the zeroes:
We are given that the sum of the zeroes is \( \sqrt{2} \). According to the formula for the sum of the zeroes, we have:
[tex]\[ -\frac{b}{a} = \sqrt{2} \][/tex]
4. Substitute the coefficients into the formula:
Substituting \( b = -k\sqrt{2} \) and \( a = 2 \) into the formula, we get:
[tex]\[ -\frac{-k\sqrt{2}}{2} = \sqrt{2} \][/tex]
5. Simplify the equation:
[tex]\[ \frac{k\sqrt{2}}{2} = \sqrt{2} \][/tex]
6. Solve for \( k \):
To isolate \( k \), multiply both sides by 2:
[tex]\[ k\sqrt{2} = 2\sqrt{2} \][/tex]
Now, divide both sides by \( \sqrt{2} \):
[tex]\[ k = \frac{2\sqrt{2}}{\sqrt{2}} \][/tex]
Simplify the right-hand side:
[tex]\[ k = 2 \][/tex]
Therefore, the value of [tex]\( k \)[/tex] is [tex]\( \boxed{2} \)[/tex].
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.